Evaluation of aquaculture of tow marine fish species in the first experimental farm of marine fish farming in Syria - Badran , Mouina M. (Iraqi Journal of Aquaculture, 2021)
In the present research, two marine fish species Chelon auratus and Siganus rivulatus were reared using a diet which contains 32 % protein for 14 months in two ponds in Alssen center of researches in Banias city of Tartous Governorate, was evaluated. The fingerlings (3 g) were collected from sea water then they were transported to two ponds (Dimensions 34 length., 5.6 width, 1.5 height meters). Fifteen thousand fingerlings were recorded in each pond. The weights, the hydrological factors, and behavior of fish were controlled. As a result, the weighs of Chelon fingerlings reached to 190 g and 93 g for Siganus, and the FCR was good (2.13, 3.33 for Chelon and Siganus respectively). Fish was quickly adaptive with the new place according to the activity of fish and accept the artificial feed in short time and ability to tolerant the different temperature and Dissolved oxygen levels, this is was clear to the population of Chelon auratus more than Siganus rivulatus.